A techno-economic analysis: Urban reconfigurable microgrids participating in short-term regulating power markets. (August 2020) - Ghaebi Panah, Payam; Hooshmand, Rahmat-Allah; Gholipour, Mehdi
Highlights: Seven European and American regulating power markets are analyzed. The case study is an urban reconfigurable microgrid including PEV, WT, PV, and TDR. Feasible revenue and profitability for different configurations are extracted. The comparison and participant-friendly rankings are concluded. Abstract: Power markets are undergoing structural alterations in accordance with emerging technologies. Traditional market rules and participants' behaviour are currently dominated by conventional power plants and synchronous generators. Renewable energy sources have gradually found their market share in the generation party specifically in developed countries. Apart from new energy resources, Demand Response Programs (DRP) have garnered attention due to substantial capabilities and potentials. This paper particularly sheds light on two flexible loads of Plugin Electric Vehicles (PEV) and cooling/heating responsive loads. PEV parking lots can be modelled as stochastic battery storages partially available for power exchange over short intervals. Besides, cooling/heating systems are naturally shiftable loads in short time horizons without deteriorating the resident's convenience. This study provides a comparative view of short-term power regulating markets in terms of bidding constraints and payment mechanisms. Consequently, a typical park & ride is considered as a reconfigurable urban microgrid to participate in short term regulating markets under different constraints. The results confirm that the internal coordination between the sub-units of microgrid brings more flexibility to enhance the total profitability. In addition, it is shown that the bidding constraints, as well as time slots, can be influential particularly in intermittent situations.